Last call at Coogan's : the life and death of a neighborhood bar - Michaud, Jon, 1967- (St. Martin's Press, 2023)
"The uniquely inspiring story of a beloved neighborhood bar that united the communities it served. Coogan's Bar and Restaurant opened in New York City's Washington Heights in 1985 and closed its doors for good in the pandemic spring of 2020. Sometimes called Uptown City Hall, it became a staple of neighborhood life during its 35 years in operation-a place of safety and a bulwark against prejudice in a multi-ethnic, majority-immigrant community undergoing rapid change. Last Call at Coogan's by Jon Michaud tells the story of this beloved saloon, from the challenging years of the late 80's and early 90's, when Washington Heights suffered from the highest crime rate in the city, to the 2010's, when gentrification pushed out longtime residents and nearly closed Coogan's itself; only a massive community mobilization led by superstar Lin-Manuel Miranda and local politicians kept the doors open. This book touches on many serious issues facing the country today: race relations, policing, gentrification, and the COVID-19 pandemic. Along the way, readers will meet the bar's owners and an array of its most colorful regulars, such as an aspiring actor from Kentucky who dreams of bringing a theater company to Washington Heights, a television reporter who loves karaoke, and a Puerto Rican community board manager who falls in love with an Irish cop from the local precinct. At its core, this is the story of one small business, the people who worked there, the customers they served, and the community they all called home"--